AMC: amyoplasia and distal arthrogryposis - Kimber, Eva (Springer Berlin Heidelberg, 2015)
Arthrogryposis multiplex congenita (AMC) is a heterogeneous condition defined as multiple congenital joint contractures in two or more body areas. The common pathogenesis is impaired fetal movements. Amyoplasia, the most frequent form, is a sporadically occurring condition with hypoplastic muscles and joint contractures. Distal arthrogryposis (DA) syndromes are often hereditary, and joint involvement is predominantly in the hands and feet. In a Swedish study, 131 patients with arthrogryposis were investigated. The most frequent diagnoses were amyoplasia and DA. In amyoplasia, muscle strength was found to be more important than joint range of motion (ROM) for motor function. In DA, muscle weakness was present in 44 % of investigated patients. The clinical findings were found to be highly variable between families and also within families with DA. Fetal myopathy due to sarcomeric protein dysfunction can cause DA. An early multidisciplinary team evaluation of the child with arthrogryposis for specific diagnosis and planning of treatment is recommended. Attention should be directed at the development of muscle strength with early stimulation of active movements. Immobilization should be minimized.